Investigation of anti-diabetic effect of a novel coenzyme Q10 derivative - Tan, Xiaojun; Yang, Xinyi; Xu, Xun; Peng, Yuwei; Li, Xin; Deng, Yongxing; Zhang, Xueyang; Qiu, Wenlong; Wu, Dudu; Ruan, Yongdui; Zhi, Chen (Frontiers in Chemistry, 2023)
A novel coenzyme Q10 derivative (L-50) was designed and synthesized by introducing a group containing bromine atom and hydroxyl at the terminal of coenzyme Q10 (CoQ10), and the antidiabetic effect of L-50 was investigated by cellular assays and animal experiments. Cytotoxicity results showed that L-50 was comparatively low toxicity to HepG2 cells. Hypoglycemic assays indicated that L-50 could increase glucose uptake in IR-HepG2 cells, with significantly enhanced hypoglycemic capacity compared to the CoQ10. In addition, L-50 improved cellular utilization of glucose through reduction of reactive oxygen species (ROS) accumulated in insulin-resistant HepG2 cells (IR-HepG2) and regulation of JNK/AKT/GSK3β signaling pathway, resulting in hypoglycemic effects. Furthermore, the animal experiments demonstrated that L-50 could restore the body weight of HFD/STZ mice. Notably, the findings suggested that L-50 could improve glycemic and lipid metabolism in HFD/STZ mice. Moreover, L-50 could increase fasting insulin levels (FINS) in HFD/STZ mice, leading to a decrease in fasting blood glucose (FBG) and hepatic glycogen. Furthermore, L-50 could recover triglycerides (TG), total cholesterol (T-CHO), lipoprotein (LDL-C) and high-density lipoprotein (HDL-C) levels in HFD/STZ mice. It is anticipated that L-50 could be a promising new agent for T2DM.